Urbanization and Social Change in Local Communities in Makassar City - Muh. Watif M; Nur Halisah; Sugiarti; Jumita; Stefani M (Pustaka Digital Indonesia, 2024)
The aim of this research is to analyze spatial physical changes. Changes in social formations, social interaction processes, and social adaptation between immigrants and local communities in new social formations and the consequences of these changes. changes in the social structure, social activities and cultural styles of local communities in Makassar today. Development and modernization are accelerated by rapid physical-spatial transformations. Occupational differentiation encourages the process of social interaction between local communities and migrant populations in new social formations. This is done within the framework of building social relationships and integrative social relations to meet basic needs and maintain existence, which conditions social change in local communities. The stratification system changes, starting from simple stratification, and then developing into economic and cultural stratification. The shift from traditional agrarian urban areas to modern urban areas is a consequence of social change.